High-dose proton therapy and tomotherapy for the treatment of sacral chordoma: a retrospective monocentric study. (1st February 2021) - Beddok, Arnaud; Saint-Martin, Caroline; Mammar, Hamid; Feuvret, Loïc; Helfre, Sylvie; Bolle, Stéphanie; Froelich, Sebastien; Goudjil, Farid; Zefkili, Sofia; Amessis, Malika; Peurien, Dominique; Cornet, Sophie; et al.
Abstract: Objective: Radiation therapy (RT) is used for the treatment of sacral chordoma, in combination with surgery or alone for unresected tumours, to improve local control (LC) and potentially overall survival (OS). The purpose of the present study was to evaluate efficacy and toxicity of proton therapy (PT), and/or intensity modulated radiation therapy (IMRT), particularly Tomotherapy, for sacral chordoma treatment. Material: Between November 2005 and June 2018, 41 consecutive patients who were not included in clinical trials, received sacral chordoma radiation treatment in Institut Curie with Tomotherapy alone in 13 patients, and combined PT and Tomotherapy boost (Proton – Tomo) in 28 patients. RT was delivered as the exclusive local treatment in 11 patients, and as a post-operative complementary treatment in 30 patients. Results: After a median follow-up of 46 months (range, 0–125 months), eight local relapses were observed, and seven patients developed distant metastasis (particularly bone and lung). The 2- and 5- year local relapse rates were 11.4% CI (0.65–22.2%) and 29% (10.5–47.4%), respectively. Over the follow-up period, ten patients died (24.4%). The estimated 2- and 5-year OS rates were 91.4% CI (82.5–100%) and 74.5% (59.4–93.5%), respectively. Fibrosis, cauda equina syndrome, and pain were the most common late toxicities. The comparison between Tomotherapy alone and Proton – Tomo revealed that acute and late cystitis were significantly more frequent in the Tomotherapy group: SHR = 0.12 IC95% (0.01–0.90 [ p = .04]), as well as late proctitis. A dosimetric comparison confirmed the interest of PT to spare rectum and bladder in this context. Conclusion: RT remains essential to improve local control in sacral chordoma. The combination of proton and photon seems to improve organ at risk sparing, resulting in a decreased rate of reported late toxicities.